The Implications of a Broken Home in Religious Character Education in Samirejo Village - Partono, Partono; Khusnussawab, Indah (IJTIMAIYA: Journal of Social Science and Teaching, 2023)
This study aims to determine the implications of a broken home in religious character education in Samirejo Kudus Village. The qualitative research method used in this study is by using a case study technique to find out more deeply and in detail about a phenomenon or problem to be studied. The results of the study show that religious character education for broken home children is by giving advice or telling in a kind and slow way, giving rewards or gifts when children want to obey and giving small punishments when children make mistakes, providing knowledge and direction as detailed as possible, as well as sending their children to Islamic-based educational institutions such as madrasas, Islamic boarding schools, and TPQ.